2007
DOI: 10.1007/978-3-540-73011-8_12
|View full text |Cite
|
Sign up to set email alerts
|

A 3D Virtual Learning Environment to Foster Communication for Long Term Ill Children

Abstract: Abstract. In this paper, we present a virtual learning environment which supports the learning process of long term sick children. By focusing on 3D Virtual Environments technology chronically ill students can still be 'telepresent' in their classroom. Analysis of existing ICT-based solutions reveal weaknesses including the absence of social involvement, the high cost of developing, and mobility issues. Our system, however, is based on concrete user needs, is educational sound and relevant, and offers a scalab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…The VLEs can connect the students to the school by overcoming the physical constraints (Beauchamp & Kennewell, 2010;Gombeir, 2007;Leask & Meadows, 2000;Zhang, Zhao, Zhou, & Nunamaker, 2004). VLEs are considered to be useful for keeping in contact with the school, classmates and for the continuation of education and social life of sick adolescents (Di Fiore, Jorissen, Vansichem, & Van Reeth, 2007;Lombaerts, Veevaete, Schuurman, Hauttekeete, & Valcke, 2006;Nicholas et al, 2007;Tielen, 2003). Previous studies suggested that the use of VLE can help chronically sick adolescents to overcome their physical barriers and keep up to date with the learning and social activities at school (Asbjørnslett & Hemmingsson, 2008;Beauchamp & Kennewell, 2010;Gombeir, 2007;Leask & Meadows, 2000;Zhang et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The VLEs can connect the students to the school by overcoming the physical constraints (Beauchamp & Kennewell, 2010;Gombeir, 2007;Leask & Meadows, 2000;Zhang, Zhao, Zhou, & Nunamaker, 2004). VLEs are considered to be useful for keeping in contact with the school, classmates and for the continuation of education and social life of sick adolescents (Di Fiore, Jorissen, Vansichem, & Van Reeth, 2007;Lombaerts, Veevaete, Schuurman, Hauttekeete, & Valcke, 2006;Nicholas et al, 2007;Tielen, 2003). Previous studies suggested that the use of VLE can help chronically sick adolescents to overcome their physical barriers and keep up to date with the learning and social activities at school (Asbjørnslett & Hemmingsson, 2008;Beauchamp & Kennewell, 2010;Gombeir, 2007;Leask & Meadows, 2000;Zhang et al, 2004).…”
Section: Introductionmentioning
confidence: 99%